The use of social media in the communication patterns of IPB University vocational school students - Mubarok, Tubagus Ahmad Naufal; Sasmita, Hari Otang; Pranata, Rici Tri Harpin; Riyanto, Sutisna (Lembaga Riset Mutiara Akbar, 2026)
Social media plays a crucial role in shaping students' increasingly rapid, flexible, and digital communication patterns. This study aims to analyze the intensity of social media use, identify the communication patterns that are formed, and examine the influence of social media use on the communication patterns of students in the Agribusiness Management Study Program, IPB Vocational School. This study used a quantitative method with a Likert scale survey technique on 91 respondents. Data were analyzed through validity, reliability, normality, linearity, and simple linear regression analysis. The results showed that the majority of students used social media with a high level of intensity, with WhatsApp, Instagram, and TikTok as the most dominant platforms used. The regression test results showed an R value of 0.565 and an R Square of 0.319, indicating that social media use had a significant effect of 31.9% on students' communication patterns. These findings confirm that social media significantly contributes to shaping the communication patterns of agribusiness students, although other factors such as direct interpersonal communication and organizational experience also influence students' overall communication patterns.